Stressors and Coping Styles of the Collegiate Athletes of PUP - Mallari, Nicolas (Social Sciences and Development Review, 2017)
This study aimed to determine the stressors and coping styles of the collegiate athletes of the Polytechnic University of the Philippines. The study was undertaken during the first semester, school year 2015-2016. Moreover, it attempted to establish significant difference in the stressors and coping styles of the respondents when they were grouped according to their personal dimensions. The descriptive survey method was used in the study. The Student Profile Checklist was employed to obtain personal profile of the respondents. Perceived Stressors Checklist which includes such variables as financial, physical, academic, intrapersonal, interpersonal, and environmental stressors and the Cope inventory were utilized to measure the stressors and coping styles of the athlete-respondents respectively. Statistical treatments such as weighted mean, one-way ANOvA, and t-test were employed in analyzing the data of the study. The participants were 90 collegiate-students of the university who were randomly selected from seven athletic events. Results showed that the athlete-respondents rated academic as well as environmental stressors as the sources of their stress. On the other hand, the athlete-respondents manage their stressors by using positive reinterpretation coping, religious coping, etc. There is a significant difference in the stressors of the respondents when they were grouped according to their personal dimensions. Likewise, the athlete-respondents differed in their coping styles when grouped according to gender, age, and family monthly income status.
Keywords: academic stressors; environmental stressors; positive reinterpretation coping; religious coping; coping styles